THE IMPACTS OF COVID-19 ON THE BRAZILIAN PENITENTIARY SYSTEM (CIPEEX, 2024)
In this article, we take a detailed look at the impacts of the COVID-19 pandemic on Brazilianprisons, with the aim of investigating the consequences of the spread of the virus in terms ofpublic health, human rights and security. Through the use of qualitative research methods,the results obtained reveal that poor hygiene conditions and overcrowding have made localprisons a favorable environment for the large-scale spread of COVID-19. The measuresadopted to contain the spread of the virus, such as the suspension of visits and outsideactivities, have exacerbated existing problems, such as social isolation and anxiety amonginmates. Given this context, it is possible to conclude that the pandemic has criticallyexposed the structural and management deficiencies of the Brazilian prison system. In thissense, we recommend the implementation of strategies such as emergency releases of nondangerous prisoners, improvements to prison facilities, including the guarantee of adequatesanitary conditions, and the adoption of strict health protocols to face this public health crisiswithout violating the fundamental rights of inmates.